Review essay: Central banking in Italy - Ivo Maes (National Bank of Belgium, 2023)
Gianni Toniolo was one of Italy's, and Europe's, foremost economic historians. Unfortunately, he suddenly passed away in November 2022, a few weeks after he had presented in Rome his newest book, the first volume of his history of the Bank of Italy, Storia della Banca d'Italia. Tomo I. Formazione ed evoluzione di una banca centrale, 1893-1943 (History of the Bank of Italy. Part I. Formation and evolution of a central bank, 1893-1943). Toniolo's history of the Bank of Italy illustrates very well many issues which are at the heart of the literature on central banking. What emerges very well is the gradual transformation of the Bank of Italy, from an emission bank to a central bank, with a growing public character of the Bank. The early relationship between the Bank of Italy and the commercial banks was often one of business rivalry and competition. Through time, the Bank of Italy gained the monopoly of the emission of banknotes but had to stop its commercial activities, while being entrusted with responsibilities in the supervision of the commercial banks. Toniolo's book covers a turbulent period in Italian monetary history, with several banking crises. Monetary policy was dominated by the issue of the reconciliation of two contrasting objectives: the exchange rate of the lira and the stability of the banking system. A distinguishing feature of the Italian experience of central banking is how the development of the Bank of Italy was embedded in the process of nation-building. In other countries, where the nation-state was established before the central bank, this was very much a process of extending the network of branches. In Italy, where the process of unification was later, it implied the merger of emission banks, a much more delicate political issue.
Keywords: E42; E58; G28; N10; 330; central banking; Bank of Italy; banking crises; financial stability; Italian lira